Academic Senate Minutes 2005-05-26 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 5/12/05 approved. Chair's Report. Academic Freedom Statement approved. Grade Appeal Policy revision approved. Honors at Graduation Policy approved. Resolution on Faculty Compensation and the Crisis in Recruiting and Retaining Faculty of High Quality in the California State University and at Sonoma State University approved. Program Review Protocol approved as interim policy that will be reviewed in the Fall. Changing of the Guard. Commendation for Susan McKillop. Good of the Order.